Short-term microgravity effects simulation does not affect fNIRS measures of cerebral oxygenation changes induced by cognitive load - Peysakhovich, Vsevolod; Kiehl, Thibault; Martinez, Lucia Vicente; Boyer, Laure; Causse, Mickaël; Paillet, Alexis; Pavy-Le Traon, Anne (Frontiers in Physiology, 2025)
In the past decade, there has been a surge in interest in space exploration studies, particularly due to the prospect of exploring distant planets such as Mars. However, long-duration space missions may pose cognitive challenges resulting from spaceflight-induced perceptual and motor changes, prolonged cephalic fluid shifts, and high cognitive load. One method for monitoring cognitive activity is functional near-infrared spectroscopy (fNIRS), a technique not yet tested under prolonged microgravity conditions beyond parabolic flight periods. Since fNIRS relies on cerebral oxygenation levels, should we adjust it for the fluid shift? To address this, the study explores the impact of simulated microgravity on cerebral oxygenation measures using fNIRS during a cognitive task, employing head-down tilt at different inclination levels and the Toulouse N-back Task (assessing memory and mental calculation) with varying difficulty levels. Eighteen subjects participated in the experiment. The results indicated that increasing difficulty levels of the cognitive task led to decreased accuracy, longer response times, and higher perceived difficulty scores. The inclination levels did not affect task performance. Increased difficulty was also concomitant with increasing HbO and decreasing HbR concentrations unaffected by the head-down tilt angle variations. These promising findings suggest that fNIRS measures could be used under microgravity conditions to measure cognitive load without correction for fluid shift.